Successful Laparoscopic Harvesting of Omental Pedicle Flap for Salvage Cerebral Revascularization in 2 Adults With Moyamoya Disease: Technique and Lessons Learned. Issue 5 (October 2017) - Schumm, Max; Simon, Kathleen; Sacho, Rapheal; Gould, Jon C.
Abstract : Moyamoya is an idiopathic and progressive disease that leads to occlusion of intracranial arteries. When other methods of revascularization fail, omentum can be used as an indirect bypass to improve cerebral perfusion. Laparoscopic mobilization of a pedicled omental flap with subcutaneous tunneling to the brain has been described in small case series in children. We report our techniques and outcomes in 2 adults with Moyamoya to undergo such a procedure. An omental flap based on the right gastroepiploic artery was created and intraoperative fluorescence imaging using indocyanine green was used to assess the viability of the flap and to guide lengthening of the pedicle. The flap was tunneled subcutaneously using skip incisions. There were no intraoperative complications and no postoperative complications related to the omental flap. Follow-up evaluation demonstrates viable omental flaps and improved cerebral vascularization. This technique is feasible in adults who require salvage cerebral revascularization for Moyamoya disease. Abstract : Supplemental Digital Content is available in the text.